A Development of Health Massage Establishments in Phetchabun Province Thailand using Appreciative Inquiry Application - Boadsaporn Anusornpanichakul; Nusaraporn Kessomboon (Indian Journal of Forensic Medicine & Toxicology, 2022)
Thai government sets a policy in order to develop Thailand as Global Medical Hub, so the Health EstablishmentAct BE 2559 was provided to regulate related business reaching the required standards. The researcher carriedout this action study by applying appreciative inquiry to develop health massage establishments in PhetchabunProvince, Thailand. The appreciative inquiry is a positive and collaborative approach to change all sizes oforganizations that techniques employed by successful entrepreneurs were used to improve unachievable ones.73 volunteer participants were included then a surveillance was conducted by finding out “superior models”which were passed all of three categories and each passed >60% as well as were passed all important drawbacksand not found any illegal performances. The five superior models employed good techniques with 8 lists: 6 listsin category 1 location and surroundings, 1 list in category 2 safety, and 1 list in category 3 service followed byassessment form of the health service standard for health massage establishment. The remaining 68 interventioncohorts implemented those techniques for 30 days. The results were passed 91.18% (62 of 68 sites) comparing to69.12% (47 of 68 sites) before implementation. Classified by each category, it was increasingly passed all of threecategories. Moreover, there are some fresh techniques were explored and used for improvement. It is assumedthat the appreciative inquiry is based on their experiences, skills, and individual exploration of entrepreneurs andmassagers to enhance their establishments reaching achievement.